(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2016)
I am a member of a group of five people in their seventies. All of us were at some time in our lives employed by the Australian Trade Union Training Authority (TUTA). We are also all members of the Australian Labor Party (ALP). We meet and plot how we can reform the ALP. We exchange short papers or long emails, and we call ourselves "The Tilters" (after Cervantes). We also lunch well and drink (a lot of) wine. We meet at a harbourside rowing club [in Sydney] which has an adequate restaurant attached and a deck with views over the water. This is not irrelevant, comrades, because the scene helps create a climate conducive to learning (to quote the egregious Malcolm Knowles). We seek meetings with various MPs, Union leaders and academics, and we even think that we have seen a change in the discourse of the Leader of the Parliamentary Labor Party that we think comes from us. We have recently decided that there is a need for a new General Theory, and are tackling that challenge in, for example, this mini-paper in which I seek to replace capitalism, socialism and the rest of it.